Upaya Pemerintah Untuk Mewujudkan Kesetaraan Kemandirian Dan Kesejahteraan Difabel Di Kabupaten Klaten ( Implementasi Peraturan Daerah Kabupaten Klaten No. 2 Tahun 2011 Tentang Kesetaraan Kemandirian Dan Kesejahteraan Difabel ) - Budi Setiyono; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
Indonesia is a country where every law that citizens have rights andobligations which should be protected by law. A right is something that is inherentto the human being, not only a perfect man but also inherent to the human beingless than perfect (disabled). This needed protection which guaranted the rights ofthe disabled to realize equality, independence and disabled priority in KlatenRegency.Regional Regulation of Klaten Regency no. 2 of 2011 on Equality,Independence, and Disabled Prosperity as the basic of law about education,health, employee, social-politics, economy, and culture for the better future ofdisabled in Klaten Regency. This study discuss about the policy study to analyzehow Klaten Regency Government actualize the regional regulation by qualitativedescriptive methode. This study was held in Klaten Regency, Central Java. Bydata collection of interview and documents.Researcher found in Regional Regulation of Klaten Regency no. 2 of 2011on Equality, Independence, and Disabled Prosperity about policy implementationvariabels that influence the implementation performance of Klaten RegencyGovernment effort to create equality and disabled prosperity. At this study, Paguyuban Penyandang Cacat Klaten (PPCK) were been the mediator to regionalregulation implementation. Factors restricting the research is not yet evenlysocialization of local regulations to the disabled and limited budgets in support ofimplementation of the change. Recommendations of the researcher is to saw thefinancial resources and cooperation between the various parties to support theimplementation of local regulations and thorough socialization from Governmentto society in order to identify their contents nor diffable of regional regulationsand created a good relationship between the Government with the disabled.Keywords: Disabled, Implementation, Klaten